2022
DOI: 10.3390/metabo12060552
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Salivary Biochemical Indicators in Primary Resectable Breast Cancer

Abstract: Despite the fact that breast cancer was detected in the early stages, the prognosis was not always favorable. In this paper, we examined the impact of clinical and pathological characteristics of patients and the composition of saliva before treatment on overall survival and the risk of recurrence of primary resectable breast cancer. The study included 355 patients of the Omsk Clinical Oncology Center with a diagnosis of primary resectable breast cancer (T1-3N0-1M0). Saliva was analyzed for 42 biochemical indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 63 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…In the early stages of BC, the significantly higher levels of urea, as well as the lowered levels of total protein and uric acid, were observed. In a similar study on patients with primary resectable breast cancer (T 1-3 N 0-1 M 0 ), Bel’skaya and Sarf [ 36 ] found that salivary levels of diene conjugate below 3.93 c.u. before treatment could be significant risk factor for tumour recurrence (HR = 1.78, 95% CI: 1.02–3.08).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the early stages of BC, the significantly higher levels of urea, as well as the lowered levels of total protein and uric acid, were observed. In a similar study on patients with primary resectable breast cancer (T 1-3 N 0-1 M 0 ), Bel’skaya and Sarf [ 36 ] found that salivary levels of diene conjugate below 3.93 c.u. before treatment could be significant risk factor for tumour recurrence (HR = 1.78, 95% CI: 1.02–3.08).…”
Section: Discussionmentioning
confidence: 99%
“… Quality assessment, including the main potential risk of bias (risk level: green—low, yellow—unspecified, red—high; quality score: green—good, yellow—intermediate, red—poor) [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. …”
Section: Methodsmentioning
confidence: 99%
“…The miRNA profile in salivary exosomes was shown to distinguish patients with lung cancer from healthy controls 11 . Salivary amino acids could be used to assess the risk of various types of cancer 12 . Although these markers have shown potential for lung cancer diagnosis, the relationship between saliva and organs far from the oral cavity needs to be comprehensively clarified.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] Salivary amino acid proling has immense potential as a non-invasive diagnostic technique in cancer research. 13 Research has demonstrated that salivary amino acids can potentially serve as biomarkers for different cancers, and variations in amino acid concentrations in body uids play a crucial role in cancer diagnosis. 14 Analyzing amino acid patterns in saliva can help doctors enhance early diagnosis, prognosis, and patient outcomes, as well as contribute to the development of customised medicines.…”
Section: Introductionmentioning
confidence: 99%